Digital Marketing Assistance for MSME Members of the Aisyiyah Branch Leadership (PCA) Colomadu Karanganyar - Subagyo, Daryono; Siti Aisyah; Handy Nugraha; Rina Trisnawati; Mujiyati, Mujiyati; Eni Setyowati; keisha Jenny Maulida Nugraha; Firlina Rizky Ramadhina (Universitas Muhammadiyah Surakarta, 2025)
This community service is carried out based on the problems faced by the Aisyah Branch Management (PCA) Colomadu Karanganyar, Central Java. The target audience needs digital marketing assistance support for members who have micro and small businesses. The problems faced by partners are the lack of complete data on the PCA Colomadu UMK profile and the lack of UMK capabilities in conducting digital promotions. The purpose of this community service activity is 1. to help the target audience in branding UMK through digital promotions, 2. Helping partners find marketing strategies that are in accordance with UMK conditions, 3. Assisting partners in improving skills to create attractive promotions, 4. Supporting partners to be able to achieve UMK performance improvement targets. The methods used in this activity are the Focus Group Discussion method, direct practice, training, and assistance. The expected output of this community service is a publication article in a journal, documentation that will be uploaded to online or offline media.